Eduardo Santos and the dead ends of the Liberal Republic - Vanegas Useche, Isidro (Universidad Pedagógica y Tecnológica de Colombia, 2015)
The public life of Eduardo Santos becomes a framework to study some of the dilemmas encountered by the Liberal Republic. Santos decisively acted upon the public scene to express a reformist liberalism which was, at the same time, cautious in its conception of the dynamics of transformations. He feared that an excessively voluntarist liberalism would carry out some necessary changes, at the expense of the stability of the republic and the return to violence, which had been kept under control during the conservative republic. His vital itinerary helps to understand this age of Colombian history, beyond the unavoidable responsibilities of some political actors.